2. a) Express \( \frac{\sqrt{3}+1}{\sqrt{3}-1}+\sqrt{3}-1 \) in the form \( a+b \sqrt{3} \) where \( a \) and \( b \) are rational numbers. b) Express \( \frac{5}{3-2 \sqrt{3}} \) in the form \( a+b \sqrt{3} \) where \( a \) and \( b \) are rational numbers.
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To tackle part a), we can start by rationalizing the expression \( \frac{\sqrt{3}+1}{\sqrt{3}-1} \). This is done by multiplying the numerator and the denominator by the conjugate of the denominator, \( \sqrt{3}+1 \): \[ \frac{(\sqrt{3} + 1)(\sqrt{3} + 1)}{(\sqrt{3} - 1)(\sqrt{3} + 1)} = \frac{(\sqrt{3} + 1)^2}{3 - 1} = \frac{3 + 2\sqrt{3} + 1}{2} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \] Now, adding \( \sqrt{3} - 1 \): \[ (2 + \sqrt{3}) + (\sqrt{3} - 1) = 2 + 2\sqrt{3} - 1 = 1 + 2\sqrt{3} \] So, the final form is: **Part a**: \( 1 + 2\sqrt{3} \). For part b), we rationalize the denominator of \( \frac{5}{3 - 2\sqrt{3}} \) by multiplying by the conjugate \( 3 + 2\sqrt{3} \): \[ \frac{5(3 + 2\sqrt{3})}{(3 - 2\sqrt{3})(3 + 2\sqrt{3})} = \frac{15 + 10\sqrt{3}}{9 - 12} = \frac{15 + 10\sqrt{3}}{-3} = -5 - \frac{10}{3}\sqrt{3} \] So, the final form is: **Part b**: \( -5 - \frac{10}{3}\sqrt{3} \).